Emotion regulation, hope, and optimism during the third wave of the COVID-19 pandemic: The role of age and personality. - Elena Carbone; Graziana Lenti; Enrico Sella; Angelica Moè; Erika Borella (PLoS ONE)
Aims This study examined age-related differences between young and older adults' emotion regulation, hope, and optimism 1 year after the COVID-19 outbreak. Whether personality explained such outcomes was also examined. Method A sample of 228 young adults and 161 older adults was interviewed in April-May 2021 to complete questionnaires assessing cognitive reappraisal (CR) and expressive suppression (ES) emotion regulation strategies use, optimism, hope (agency and pathways components), and personality traits. Results Older adults reported greater CR and ES use, optimism, and hope-agency levels than young adults, whereas no age differences emerged for hope-pathway scores. Personality traits (more consistently emotional stability) contributed to explaining CR and ES use, and greater hopeful and optimistic dispositions. Conclusions These findings confirm older adults' advantage in facing the emotional and psychological fallout of the COVID-19 pandemic in its third wave. They also underscore the importance of considering personality to depict individual profiles prone to experiencing long-term negative emotional/psychological consequences of emergencies as COVID-19.